ANALISIS PERTUMBUHAN PENDAPATAN ASLI DAERAH (PAD) DI KOTA BOGOR DENGAN PENDEKATAN TIPOLOGI KLASSEN - Widianti, Meida; Setiawan, Ade Budi; Didi, Didi (Komunitas Manajemen Kompetitif, 2024)
Bogor City is one of the regional governments that collects Regional Original Income (PAD) from the community and then gives it back to the community to improve the area and provide better services. The city of Bogor is also one of the five large cities with the highest economic growth in West Java. However, in 2018 and 2020, Bogor City's PAD experienced a decline from the previous year, this was caused by several PAD component factors, namely regional taxes, regional levies, results of separated regional wealth management, and other legitimate PAD which also experienced a decline. This research was conducted to analyze the class typology used to classify the PAD components of Bogor City. The research results show that in quadrant I (prime) 22 of the 29 types of regional tax components are fulfilled or around 75.8%, quadrant II (potential) 3 of the 24 types of tax components are 10.4% fulfilled, quadrant III (developing) there is 1 out of 29 types of regional tax components 3.45% fulfilled and quadrant IV (underdeveloped) with 3 out of 29 types of tax components 10.4% fulfilled of the total regional taxes in Bogor City.